Empirical welfare analysis in random utility models of labour supply - André Decoster; Peter Haan (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The aim of this paper is to apply recently proposed individual welfare measures in the context of random utility models of labour supply. Contrary to the standard practice of using reference preferences and wages, these measures preserve preference heterogeneity in the normative step of the analysis. They also make the ethical priors, implicit in any interpersonal comparison, more explicit. On the basis of microdata from the Socio Economic Panel (SOEP) for married couples in Germany, we provide empirical evidence about the sensitivity of the welfare orderings to different normative principles embodied in these measures. We retrieve individual and household specific preference heterogeneity, by estimating a structural discrete choice labor supply model. We use this preference information to construct welfare orderings of households according to the different metrics, each embodying different ethical choices concerning the preference heterogeneity in the consumption-leisure space. We then discuss how sensitive the assessment of a hypothetical tax reform is to the choice of metric. The chose tax reform is similar to a subsidy of social security contributions.
Keywords: C35; D63; D78; H24; H31; J22; 330; Welfare measures; labour supply; random utility; preference heterogeneity; Wohlfahrtseffekt; Arbeitsangebot; Präferenztheorie; Haushaltsökonomik; Deutschland